(untitled) (Revista Dialectus - Revista de Filosofia, 2018)
This article, broadly speaking, presents the XXI century socialism elaborated and enforced by President Hugo Chavez Frias. If socialism is the sole system that permits the eradication of the afflictions from which humanity suffers, one needs to learn from XXI century socialist experience to build it, considering the peculiarities of each country and the form of capitalism in its new imperialistic phase.